2008
DOI: 10.1124/mol.108.050831
|View full text |Cite
|
Sign up to set email alerts
|

Cu/Zn Superoxide Dismutase Typical for Familial Amyotrophic Lateral Sclerosis Increases the Vulnerability of Mitochondria and Perturbs Ca2+Homeostasis in SOD1G93AMice

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disorder characterized by the selective loss of defined motoneuron populations in the brainstem and spinal cord. Although low cytosolic calcium ([Ca 2ϩ ] i ) buffering and a strong interaction between metabolic mechanisms and [Ca 2ϩ ] i have been associated with selective motoneuron vulnerability, the underlying cellular mechanisms are barely understood. To elucidate the underlying molecular events, we used rapid chargecooled device imaging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
76
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 58 publications
4
76
0
Order By: Relevance
“…The calcium-sensitive fluorescent dye was introduced into C2C12 cells by adding 2 μM of cell membrane-permeable Fluo-4/ AM (Invitrogen) into the media of the culture plates followed by incubation at 37°C, 5% CO 2 for 40 min. Cells were rinsed with DMEM and incubated for 20 min at 37°C to allow for complete deesterification (for details see Jaiswal and Keller, 2009 MicroImaging, Germany). In brief, experiments were performed as previously described (Bergmann and Keller, 2004;Jaiswal and Keller, 2009) using a Zeiss LSM 7 MP system, consisting of an Axio Examiner.Z1 microscope (Carl Zeiss MicroImaging, Germany), Ti:sapphire Chameleon Vision, 2-photon mode-locked laser system operated at 800 nm (680 nm-1080 nm tuning range,~80 MHz; 3.3 W peak power , Coherent, Inc., Auburn, CA) and controlled by Zen 2009 software (Zeiss, Germany).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcium-sensitive fluorescent dye was introduced into C2C12 cells by adding 2 μM of cell membrane-permeable Fluo-4/ AM (Invitrogen) into the media of the culture plates followed by incubation at 37°C, 5% CO 2 for 40 min. Cells were rinsed with DMEM and incubated for 20 min at 37°C to allow for complete deesterification (for details see Jaiswal and Keller, 2009 MicroImaging, Germany). In brief, experiments were performed as previously described (Bergmann and Keller, 2004;Jaiswal and Keller, 2009) using a Zeiss LSM 7 MP system, consisting of an Axio Examiner.Z1 microscope (Carl Zeiss MicroImaging, Germany), Ti:sapphire Chameleon Vision, 2-photon mode-locked laser system operated at 800 nm (680 nm-1080 nm tuning range,~80 MHz; 3.3 W peak power , Coherent, Inc., Auburn, CA) and controlled by Zen 2009 software (Zeiss, Germany).…”
Section: Chemicalsmentioning
confidence: 99%
“…Cells were rinsed with DMEM and incubated for 20 min at 37°C to allow for complete deesterification (for details see Jaiswal and Keller, 2009 MicroImaging, Germany). In brief, experiments were performed as previously described (Bergmann and Keller, 2004;Jaiswal and Keller, 2009) using a Zeiss LSM 7 MP system, consisting of an Axio Examiner.Z1 microscope (Carl Zeiss MicroImaging, Germany), Ti:sapphire Chameleon Vision, 2-photon mode-locked laser system operated at 800 nm (680 nm-1080 nm tuning range,~80 MHz; 3.3 W peak power , Coherent, Inc., Auburn, CA) and controlled by Zen 2009 software (Zeiss, Germany). The system was equipped with a X-Cite 120 lamp for reflected light illumination and water immersion objectives (10× achroplan and 20× plan-apochromat, 40× plan-apochromat, 0.30, 1.0 and 0.8 NA respectively, Zeiss; Germany).…”
Section: Chemicalsmentioning
confidence: 99%
“…Mitochondria from these mouse models of human ALS show increased vulnerability and impaired Ca 2+ homeostasis [180] that precedes the onset of motor symptoms [181]. In fact, while the wild-type protein is anti-apoptotic, mutSOD1 seems to promote the mitochondrial apoptotic pathway.…”
Section: Amyotrophic Lateral Sclerosis (Als)mentioning
confidence: 99%
“…high -mSOD1 mouse motor neurons have been seen also by different Ca 2+ detection methods [183,184]. Recent work on a mouse neuromuscular junction preparation has shown that mitochondrial Ca 2+ accumulation is accompanied by greater mitochondrial depolarization, specifically within motor neuron terminals of human mutant SOD1 Tg mice [185].…”
Section: Lj Martin / Mitochondria In Neurodegenerative Diseasesmentioning
confidence: 99%